Assessing the Legality of Coercive Restructuring Tactics in UK Exchange Offers - Robert Peel (UCL Journal of Law and Jurisprudence, 2015)
This article discusses bondholder exchange offers, a useful private debt-restructuring technique. In a typical offer, an under‑performing issuer will seek to exchange its old bonds for new bonds with economically less favourable terms to bondholders, thus deleveraging the issuer without the difficulties of a formal insolvency process. Some issuers seek to incentivise their bondholders to accept these new, less favourable bonds by using coercive tactics, such as ‘exit consents’ and ‘covenant strips’. While lawful in the US, the English courts have only recently considered them for the first time in relation to English Law bonds. The Assénagon case declared an egregious coercive tactic invalid on the basis of an old company law principle, casting doubt on the validity of other coercive tactics. This principle (the’abuse principle’) originally restricted the abuse of minority shareholders by the majority, but is now also applicable to debt security voting arrangements. This article examines the abuse principle through the cases and discusses its potential application to other forms of coercive tactics in exchange offers. The article argues that where a coercive tactic is used purely to compel bondholders to exchange their bonds, this will contravene the abuse principle. The use of coercive tactics may however still be consistent with the abuse principle and Assénagon. An issuer will need to show that ‘reasonable men’ could see the tactic as beneficial for the class of bondholders, even though its use might adversely affect non‑exchanging bondholders. A potential permissible example is a covenant strip that removes a restriction on asset disposals in order to facilitate a disposal pursuant to a restructuring. >> Read full article